Pengaruh Electronic Word of Mouth dan Security Terhadap Buying Decision Melalui Electronic Trust Sebagai Variabel Media - Leli Alfiani; Ambar Lukitaningsih; Bernadetta Diansepti Maharani (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
The rapid development of technology has made business competition in the e-commerce sector even tighter. Consumer purchasing decision making is influenced by several factors such as Trust Online. Tokopedia is an Indonesian company that is engaged in e-commerce. The problems of this research are worry, uncertainty and fear of the risks received when faced withshopping online. For this reason, in this study, the researcher wanted to know what factors influence generation Y. Researchers narrowed down three variables, E-Wom, Security, E-Trust This study used a quantitative research type and selected 150 people (male & female, 18-28 years old, and using e-commerce Tokopedia) as research subjects. Researchers used the SPSS application to test the results of the study. The results showed that the most influencing factor in influencing purchasing decisions when doingshopping online application-basedwas Electronic Trust, followed by Electronic Word Of Mouth, and the last which had the least effect was Security. Keywords: E-commerce, E-Wom, Security, E-Trust, Buying Decision